A brief history of Iraq [ - Fattah, Hala Mundhir , 1950-; Caso, rank (Facts On Fil, 2009)
From the Publisher: The story of Iraq is that of a people struggling to overcome the burdens of a turbulent past. From the ancient Mesopotamian civilizations to the 2003 U.S. invasion and subsequent fall of Saddam Hussein, A Brief History of Iraq takes